(untitled) (Patan Pragya, 2020)
Nepal has much diversified climate topographical condition; variety of agricultures’ farming is possible in different climate. For the development of the Nepalese agriculture different cash crops played a vital role in the different geographical and climate condition. Middle hilly area from eastern part to western part of Nepal climate is suitable for Coffee farming. This research examines the problems and prospects of the coffee cultivation in Nepal with special reference to Hokse Bazaar of Kevrepalanchok district. The objectives of this study are to analyze the present situation of Coffee cultivation in the sample areas population and to analyze problems and prospects of the coffee cultivation in the areas. Both primary and secondary data are used the sources of information. Descriptive research design has been used for the processes of data analysis. This research shows the increasing Coffee farming people who help to improve the local people’s economic status and the protection of landslides as well as environment. There are many problems such as technical, economy for investment, proper market and Coffee refinement. To solve different problems of Coffee cultivation government of Nepal must support them.